Spillovers from the ECB's non-standard monetary policy measures on south-eastern Europe - Isabella Moder (European Central Bank (ECB), 2017)
This paper is the first to comprehensively assess the impact of the euro area's non-standard monetary policy measures on south-eastern Europe. By employing bilateral BVAR models, I am able to estimate the response of output and prices for each country, as well as to shed more light on potential shock transmission channels. The results suggest that the ECB's non-standard monetary policy measures have had pronounced price effects on all south-eastern European countries, and output effects on approximately half of them. While I also find exports to be a relevant transmission channel in most cases, the interbank market rate responds significantly only in a few cases as the region was subject to significant cross-border bank deleveraging after the crisis. Furthermore, the results suggest that the exchange rate regime does not play a role in determining the sign and magnitude of price level and output responses. This is in line with the absence of distinct exchange rate responses in the model output, suggesting that exchange rates did not act as buffers for spillovers of euro area non-standard monetary policy measures on south-eastern Europe.
Keywords: C11; C32; E52; F42; 330; Unconventional monetary policy; international shock transmission; BVAR; EU integration